Vivencias de los escolares que sufren maltrato familiar. Un enfoque fenomenológico. Trujillo, 2008 - Nieto León, Sandra Verónica (2009)
This study qualitative in nature, phenomenological trajectory was to unveil the phenomenon that experience schoolchildren who suffer maltreatment family. For this purpose the research subjects were five schoolchildren from 10 to 12 years attending primary and family who suffered abuse.The speeches were obtained through proper interaction, raising the question norteadora What are the experiences of (as) school to be abused (as) by his father, mother and / or caregiver (a)?. For the analysis of speeches followed the procedure outlined by Edmund Husserl and that was the description, phenomenological reduction, analysis and ideographic nomothetic analysis; We obtained nine categories: sadness, incomprehension, anger, loneliness, guilt, pain, rejection and disaffection. Consideration was given to the family and social influence in this situation, it was considered that the phenomenon reveals that the experience of school children who suffer maltreatment family is the evil-being by the existential condition that places those schools.